Discontinuity of Breastfeeding Care: “There's No Captain of the Ship” - Garner, Christine D. (Breastfeed Med, 2016)
Background: Breastfeeding rates in the United States are suboptimal. Health professionals (HPs) have a unique opportunity to support breastfeeding because of the frequency and timing of their visits with mothers and infants as well as their call by professional organizations to do so. The objective of this study was to understand HPs' perceived roles and experiences with providing breastfeeding-related care. Materials and Methods: In-depth qualitative interviews were conducted with 34 HPs (obstetricians, midwives, pediatricians, nurses, and lactation consultants) who care for pregnant or lactating women. Interviews were audio-recorded, transcribed, and verified for accuracy; content analysis was used to identify themes using a grounded theory approach. Results: The overarching theme was discontinuity in breastfeeding care across the continuum. Most HPs relied on other HPs to provide breastfeeding care, which resulted from and contributed to problematic gaps in care that were reported. A minority of HPs attempted to bridge gaps in breastfeeding care or improve continuity. Contributing to the discontinuity were a lack of time, lack of skills, inconsistent messages, and low communication across stages of care. HPs were unsure whether their help was effective and whether required follow-up was completed. Conclusions: Despite HPs' recognition of breastfeeding as the best choice for infant feeding, breastfeeding care may be disjointed and a barrier to achieving breastfeeding recommendations. These problems should be investigated and systemically addressed in future research so that maternal–infant dyad breastfeeding care can be improved.